Meaning in Life as Mediator of Family Allocentrism and Depressive Symptoms Among Chinese and Italian Early Adolescents. Issue 2 (March 2021) - Germani, Alessandro; Delvecchio, Elisa; Li, Jian-Bin; Lis, Adriana; Mazzeschi, Claudia
Establishing a coherent meaning in life has long been considered to be a protective factor of well-being, but this construct has been understudied in early adolescent development. The current study investigated the relationships between family allocentrism and depressive symptoms as well as the mediation effect of meaning in life in 214 Chinese and 201 Italian early adolescents. Although family allocentrism was higher in Chinese than Italian participants, it was significantly associated to lower depressive symptoms in both countries. Moderated mediational analyses showed that in both countries: (a) family allocentrism was positively related with presence of meaning; (b) family allocentrism and presence of meaning were negatively related to depressive symptoms; and (c) presence of meaning mediated the relationship between family allocentrism and depressive symptoms. In conclusion, family allocentrism and presence of meaning in life are important preventive factors of early adolescents' depressive symptoms in both collectivistic and in individualistic countries.